2015
DOI: 10.12816/0027069
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Design Approach for Xylanase Production by Aspergillus Niger Using Soybean Hulls : Optimization and Determining the Synergistic Effects of Medium Components on the Enzyme Production

Abstract: Xylanases are hydrolytic enzymes produced by different microorganisms which convert xylooligomers to its constituent xylose units. The growing interests in xylanase production could be linked to its diverse industrial applications. The use of agricultural residues contributed in overcoming one of the major challenges of enzyme production, which is the production cost. This study involves the use of Face centered central composite design (FCCCD) under Response surface methodology (RSM) to optimize the medium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Obtained results were greater than those of Park et al (2002) who denoted that the enhanced xylanase activity of 0.5 U/ml, using rice straw by A. niger culture, was achieved by fractional factorial design of optimization medium conditions and process parameters. As well, the present results were the most close to those obtained by Salihu et al (2015) who reported that the maximum xylanase activity varied from 1.00 to 1.5 U/ml, using soybean hulls by A. fumigatus NITDGPKA3 and A. niger, respectively, using statistical methods.…”
Section: Optimization Of Medium Components For Xylanase Productionsupporting
confidence: 91%
“…Obtained results were greater than those of Park et al (2002) who denoted that the enhanced xylanase activity of 0.5 U/ml, using rice straw by A. niger culture, was achieved by fractional factorial design of optimization medium conditions and process parameters. As well, the present results were the most close to those obtained by Salihu et al (2015) who reported that the maximum xylanase activity varied from 1.00 to 1.5 U/ml, using soybean hulls by A. fumigatus NITDGPKA3 and A. niger, respectively, using statistical methods.…”
Section: Optimization Of Medium Components For Xylanase Productionsupporting
confidence: 91%
“…The influence of di-potassium salt, K 2 HPO 4 , and its concentrations on endoxylanase production were determined and it was found that increased (2191.28 U/g DR) endoxylanase production was obtained by addition of 0.5% K 2 HPO 4 in moistening medium (Table 1). Salihu et al (2015) also reported that K 2 HPO 4 was one of most important components for obtaining maximum xylanase production from Aspergillus niger AS-1. Jeya et al (2005) also found that K 2 HPO 4 significantly increased the production of endoxylanase from Aspergillus versicolor MKU3.…”
Section: Optimization Of Culture Conditions In Ssfmentioning
confidence: 95%
“…The optimization production of lipase by utilizing POME-based medium was achieved by using FCCCD under response surface methodology (RSM) [38], [39]. The design was used to determine the interaction as well as to optimize three independent quantitative variables viz ; sodium nitrate (X1), Tween-80 (X2) and di-potassium hydrogen phosphate (X3) which were identified to exhibit most significant positive effect following PB and OFAT screening.…”
Section: Methodsmentioning
confidence: 99%